O sentido da salvação: ministério público federal e o processo de construção da agenda anticorrupção no Brasil (1988-2022) - Lima, Arthur Ives Nunes da Mota (2024)
In different contexts of the brazilian republican period, a series of generational and institutional transformations could be highlighted in the development of the federal Prosecutor's Office in Brazil. Born under a political’s domination, its conditions of professional exercise and institutional autonomy were shaped by the chains of events that marked the Brazilian political environment. However, from 1988 onward, in the context of the country's redemocratization, the Brazilian Prosecutor’s Office began to experience a kind of institutional rebirth: its transition from a condition of greater subordination to the political authority to a more proactive profile in the dynamics of the political system and assuming a role as a direct defender of diffuse social interests. Under these circumstances, the present study sought to analyze the social, institutional, and political conditions that allowed the aforementioned process of transformation in the profile of the Brazilian Prosecutor's Office. The development of the anti-corruption agenda by the parquet, in this scenario, will be used as a conduit to this interpretation, given its consolidating role in this transformation process by allowing a more precise translation of a new relational meaning established between the prosecutor's office and politics arena in the post-88 redemocratization period of Brazil.